Sociodemographic, maternal and clinical conditions of children exposed to the human immunodeficiency virus - Marli Teresinha Gimeniz Galvão; Gilmara Holanda da Cunha; Julyana Gomes Freitas; Elucir Gir; Renata Karina Reis (Universidade Federal do Ceará, 2014)
This was a quantitative, descriptive cross-sectional study aiming to identify the sociodemographic, maternal and clinical conditions of children exposed to the Human Immunodeficiency Virus, who were treated in a reference hospital for infectious diseases in Fortaleza-Ceará. The sample consisted of 117 mothers who brought their children for consultation between July and December 2009. Data were collected through a semi-structured interview form. There was a higher percentage of mothers aged 20-29 years (53.8%), married (73.5%) and unemployed (68.3%). Most children were less than 12 months old (39.4%), did not receive governmental assistance (66.6%), and did not attend the health service on the scheduled date (77.0%). Some mothers did not use Zidovudine during pregnancy (15.4%), and eight children did not use it after birth (6.8%). Nineteen children did not use prophylaxic Trimethoprim-Sulfametaxazol in the first year of life. It was concluded that most children had socioeconomic difficulties that negatively influenced their health conditions.